Effects of biochar and activated carbon on biogas generation: A thermogravimetric and chemical analysis approach. (1st January 2020) - Rasapoor, M.; Young, B.; Asadov, A.; Brar, R.; Sarmah, Ajit K.; Zhuang, W.-Q.; Baroutian, S.
Highlights: Using 20 g/L biochar-additive changed the TG pattern, in favour of the AD process. Biochar improved AD process by maintaining ammonia nitrogen below 650 mg/L. There was no relationship between biochar physical properties and biogas yield. 10 g/L AC and 30 g/L biochar additives were found more effective on AD process. Abstract: Applying carbon-based additives can be an ideal strategy to maximise biogas yield, due to low operating costs and high adaptability to large scale implementation. Although several studies have revealed the positive impact of carbon-based additives on biogas generation, the mechanisms and reasons behind this have not yet been comprehensively studied for anaerobic digestion of organic waste. The mechanism of direct interspecies electron transfer (DIET) has been widely used to describe the effect of carbon-based additives on anaerobic processes. However, there are other mechanisms which are associated with this process. In this study, activated carbon and biochar were used as additives in anaerobic digestion (AD) of the organic fraction of municipal solid waste. Thermogravimetric, physical and chemical analyses were conducted to investigate the effect of these additives on the degradation process. The results showed a direct relationship between the thermogravimetric characteristics and the reaction rate. Using 20 g/L biochar significantly increased the rate of AD for all types of biochar, as confirmed by the thermogravimetric results. The physical properties of the additives, including electrical conductivity and surface area, were found to influence only the rate of AD process and not the biogas production yield. Biochar showed more promising results in terms of biogas generation compared to activated carbon due to its ability to adsorb ammonia nitrogen. Although activated carbon efficiently increased the organic degradation rate, concentrations higher than 10 g/L dramatically increased the ammonia nitrogen concentration, which resulted in hindering the methanogenic bacteria activity due to its inhibitory effect. As a result, biogas generation yield did not increase using a high concentration of activated carbon.